(untitled) (Progressive Agriculture, 2015)
Disposal of spent mushroom substrate (SMS) generated by the mushroom production industry has an adverse effect on the environment which leads to a deterioration of soil, air and water quality. Scope exists to use this substrate to produce good quality compost. The present study was done to assess the quality of SMS compost through evaluation of their characteristics and the chemical changes that occur during composting. Physical, chemical and microbial characteristics were determined by observing color, moisture (%), size reduction, weight loss, pH, EC, different nutrient contents and abundance of E. coli and Salmonella spp. The result showed an increasing trend for the pH, N, P& S concentration and a decreasing trend for EC, OC & C/N ratio during composting period. As determined, the pH value (7.38) and the C/N ratio (21) were within the recommended range that used in different countries. The concentrations of N, P, K, S, Ca, Mg, Fe, Mn & B were measured as 1.17%, 0.08%, 1.04%, 0.11%, 2.76%, 0.43%, 0.51%, 0.03% and 0.01%, respectively, all of which were within the recommendation limits. Heavy metals such as Zn, Cu and Ni contents were recorded as 0.007%, 0.001%, and 0.33 ppm, respectively showing their values within the maximum allowable limits. The concentration of Pb and Cd was below the detection limit. The SMS compost was free of E. coli and Salmonella spp. Hence, all these properties indicate that the SMS can be effectively used to produce good quality compost. Progress. Agric. 2014. 25: 1-8